Effects of environmental orientation and environmental knowledge on the willingness to reduce plastic waste among Gen Z in Indonesia and Thailand - Weni Rosdiana; Agus Prastyawan; Yuni Lestari; Lena Citra Manggalasari; Haryo Kunto Wibisono; Pattanapong Topark-ngarm; Farika Nikmah (Environmental Economics)
The purpose of this study is to explore the willingness to reduce plastic waste analyzing the effect of environmental orientation and environmental knowledge. The analysis was conducted at three universities, with respondents being 430 students who are categorized as Gen Z. The universities involved are State University of Surabaya, State Polytechnic of Malang, Indonesia, and College of Local Khon Kaen University, Thailand. Using path analysis, the paper revealed that environmental orientation and environmental knowledge significantly influence the willingness to reduce plastic waste. All variables used in the research model are significant for both the outer and inner models. This study confirms a positive and significant influence on the relationship between independent variables, as well as between independent and dependent variables. All relationships produce T statistic > T table (1.96). Environmental knowledge is positively and significantly influenced by environmental orientation by 32% (TStat = 3.535), willingness to reduce plastic waste (TStat = 6.874) is influenced by environmental orientation by 50%, and willingness to reduce plastic waste (TStat = 5.454) is influenced by environmental knowledge by 41%. The findings of this study are important, considering that Gen Z will be decision-makers not only for personal interests in their consumption behavior but also for Gen Z’s position as policymakers in the future.